Scientific advice related to nutrient profiling for the development of harmonised mandatory front‐of‐pack nutrition labelling and the setting of nutrient profiles for restricting nutrition and health claims on foods. (19th April 2022) - ,; Turck, Dominique; Bohn, Torsten; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Peláez, Carmen; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver scientific advice related to nutrient profiling for the development of harmonised mandatory front‐of‐pack nutrition labelling and the setting of nutrient profiles for restricting nutrition and health claims on foods. This Opinion is based on systematic reviews and meta‐analyses of human studies on nutritionally adequate diets, data from the Global Burden of Disease framework, clinical practice guidelines, previous EFSA opinions and the priorities set by EU Member States in the context of their Food‐Based Dietary Guidelines and associated nutrient/food intake recommendations. Relevant publications were retrieved through comprehensive searches in PubMed. The nutrients included in the assessment are those likely to be consumed in excess or in inadequate amounts in a majority of European countries. Food groups with important roles in European diets have been considered. The Panel concludes that dietary intakes of saturated fatty acids (SFA), sodium and added/free sugars are above, and intakes of dietary fibre and potassium below, current dietary recommendations in a majority of European populations. As excess intakes of SFAs, sodium and added/free sugars and inadequate intakes of dietary fibre and potassium are associated with adverse health effects, they could be included in nutrient profiling models. Energy could be included because a reduction in energy intake is of public health importance for European populations. In food group/category‐based nutrient profiling models, total fat could replace energy in most food groups owing to its high‐energy density, while the energy density of food groups with low or no fat content may be well accounted for by the inclusion of (added/free) sugars. Some nutrients may be included in nutrient profiling models for reasons other than their public health importance, e.g. as a proxy for other nutrients of public health importance, or to allow for a better discrimination of foods within the same food category.